2014
DOI: 10.1038/onc.2014.133
|View full text |Cite
|
Sign up to set email alerts
|

Less understood issues: p21Cip1 in mitosis and its therapeutic potential

Abstract: p21(Cip1) is a multifunctional protein and a key player in regulating different cellular processes. The transcription of p21 is regulated by p53-dependent and -independent pathways. The expression of p21 is increased in response to various cellular stresses to arrest the cell cycle and ensure genomic stability. p21 has been shown to be a tumor suppressor and an oncogene as well. The function of p21 in mitosis has been proposed but not systematically studied. We have recently shown that p21 binds to and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 168 publications
(233 reference statements)
2
106
0
Order By: Relevance
“…A potential AD biomarker in lymphocytes seems to be the p21 protein, one of the most significant regulators of the G1/S checkpoint and the mediator of cell cycle arrest in the G1 phase [55]. In SAD lymphocytes an impaired progression of the G1/S phase occurs, consistent with p21's main change and its known function in arresting G1 [17].…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 72%
See 1 more Smart Citation
“…A potential AD biomarker in lymphocytes seems to be the p21 protein, one of the most significant regulators of the G1/S checkpoint and the mediator of cell cycle arrest in the G1 phase [55]. In SAD lymphocytes an impaired progression of the G1/S phase occurs, consistent with p21's main change and its known function in arresting G1 [17].…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 72%
“…A few groups demonstrated a specific failure of the G1/S transition checkpoint in lymphocytes of AD patients (reviewed in [46]). This supports the AD cell cycle hypothesis of mitosis failure and validates using peripheral blood cells to study AD pathogenesis' molecular basis and search for AD biomarkers.A potential AD biomarker in lymphocytes seems to be the p21 protein, one of the most significant regulators of the G1/S checkpoint and the mediator of cell cycle arrest in the G1 phase [55]. In SAD lymphocytes an impaired progression of the G1/S phase occurs, consistent with p21's main change and its known function in arresting G1 [17].…”
mentioning
confidence: 72%
“…The Cdk-interacting protein p21 Cip1/CDKN1A (p21) plays key roles in a broad range of cellular events like cell cycle regulation, apoptosis, differentiation, cytoskeletal dynamics, cell migration, gene transcription, DNA repair, reprogramming of induced pluripotent stem cells, aging and onset of senescence [1]. The transcription of p21 is regulated by p53-dependent [2] as well as -independent pathways [3].…”
Section: Introductionmentioning
confidence: 99%
“…Another vital negative regulator is tumor suppressor p53, which is an essential downstream target of AMPK. Increased expression of p53 induces cell cycle arrest and/or apoptosis by modulating CDKs and CDKIs [47,48]. Previous studies have shown that AMPK activation upregulates the expression of p53 and p21 and down-regulates the expression cyclin E/CDK2, thus preventing cell cycle progression into S phase [49].…”
Section: Discussionmentioning
confidence: 99%